Malaria and Dengue: Assessment of Knowledge among Households in Rural Sindh, Pakistan. - Muzammil Pervaiz Khan; Farhan Ahmad; Ahsan Ashfaq; Syed Hasan Danish; Syed Mohammed Ali Warsi; Aneeta Iqbal Khan (Journal of the Dow University of Health Sciences, 2015)
Objectives: To assess knowledge and attitude about malaria and dengue, its spread, symptoms and prevention among the population of Dadu and Badin district of Sindh province. Study Design and Methods: A cross sectional baseline survey was conducted in rural areas of Dadu and Badin districts of Sindh in 2014. Cluster sampling technique was utilized for selection of 900 households from two union councils. Personal interviews were conducted by trained data collectors on pretested questionnaire. Data was entered on SPSS version 20. Descriptive analysis was conducted. Results: Only 22.4% in Dadu and 34.4% of Badin residents heard about dengue fever. Merely13% from both districts knew about bleeding in dengue fever. Only 17.9% in Dadu and 25% in Badin opined that malaria occurred post rainfall. Only3.5% in Dadu and 2.9% in Badin had the perception that malaria incurred after floods. In Badin only 3% had ever sprayed inside their homes compared to 7% in Dadu in past one year. In Badin 84% were using mosquito nets as prevention while in Dadu 66%. Only 3.5% in Dadu and 6.2% were covering water buckets as a precautionary measure against mosquitoes. Conclusion: In the present survey, situation is alarming as there are gross deficiencies in knowledge and attitudes pertaining to malaria and dengue while preventive practices are negligible.